Does hydroxychloroquine improve patient reported outcomes in patients with lupus?. (October 2021) - Jolly, Meenakshi; Sehgal, Vinay; Arora, Shilpa; Azizoddin, Desiree; Pinto, Benzeeta; Sharma, Aman; Devilliers, Herve; Inoue, Mitsuyo; Toloza, Sergio; Bertoli, Ana; Blazevic, Ivana; Vilá, Luis M; et al.
Background: Hydroxychloroquine (HCQ) use is associated with less disease activity, flares, damage and improved survival in Systemic Lupus Erythematosus (SLE). However, its effect on patient reported health outcomes (PROs) such as quality of life (QOL) is not known. Methods: International data from Study on Outcomes of Lupus (SOUL) from 2, 161 SLE patients were compared by HCQ use. Disease activity and damage were assessed using SELENA-SLEDAI and SLICC-ACR/SDI. QOL was evaluated using LupusPRO and Lupus Impact Tracker (LIT). Linear regression analyses were performed with LupusPRO summary scores health related HRQOL, non-health related NHRQOL and LIT as dependent and HCQ use as independent variable. Analyses were undertaken to test mediation of effects of HCQ use on QOL through disease activity. Results: Mean age was 40.5 ± 12.8 years, 93% were women. Sixty-three (1363/2161) percent were on HCQ. On univariate analysis, HCQ use was associated with (a) better QOL (LupusPRO-HRQOL: β 6.19, 95% CI 4.15, 8.24, P ≤ 0.001, LupusPRO NHRQOL: β 5.83, 95% CI 4.02, 7.64, P ≤ 0.001) and less impact on daily life (LIT: β −9.37, 95% CI −12.24, −6.50, P ≤ 0.001). On multivariate and mediational analyses, the effects of HCQ on QOL were indirectly and completely mediated through disease activity. Conclusions: HCQ use in SLE is associated with better patient reported health outcomes (LupusPRO-HRQOL and NHRQOL and impact on daily life), and the effects are mediated through disease activity. This information can facilitate patients and physician's communication with decision-making regarding the use of HCQ for SLE management.